2019
DOI: 10.1177/0018720818824253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gesture-Based In-Vehicle Interaction: User Experience and the Potential to Reduce Driver Distraction

Abstract: Objective: We observe the effects of in-vehicle system gesture-based interaction versus touch-based interaction on driver distraction and user experience. Background: Driver distraction is a major problem for traffic safety, as it is a contributing factor to a number of accidents. Visual distraction in particular has a highly negative impact on the driver. One possibility for reducing visual driver distraction is to use new forms of interaction in the vehicle, such as gesture-based interaction. Method: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…A number of interaction studies have been conducted on infotainment systems. Various infotainment systems have been studied, such as touch buttons (Crundall et al, 2016;Feng et al, 2018;Kim et al, 2014;Suh & Ferris, 2019), overall user interface (UI) elements (Hua & Ng, 2010;Naujoks et al, 2019;Pankok & Kaber, 2018), icons/symbols (Silvennoinen et al, 2017), screen position (Kuiper et al, 2018), layout (Kim et al, 2015;Li, Chen et al, 2017), sound effects (Larsson & Niemand, 2015), gestures (Graichen et al, 2019;Parada-Loira et al, 2014), and modality (Gaffar & Kouchak, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of interaction studies have been conducted on infotainment systems. Various infotainment systems have been studied, such as touch buttons (Crundall et al, 2016;Feng et al, 2018;Kim et al, 2014;Suh & Ferris, 2019), overall user interface (UI) elements (Hua & Ng, 2010;Naujoks et al, 2019;Pankok & Kaber, 2018), icons/symbols (Silvennoinen et al, 2017), screen position (Kuiper et al, 2018), layout (Kim et al, 2015;Li, Chen et al, 2017), sound effects (Larsson & Niemand, 2015), gestures (Graichen et al, 2019;Parada-Loira et al, 2014), and modality (Gaffar & Kouchak, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, complex IVISs provide various types of information, such as entertainment information, in addition to information directly related to driving, and these types of systems involve manual control using physical buttons. Recently, several studies have been conducted on the visual area of touch screen-type infotainment systems (Graichen et al, 2019;. However, unlike clusters and HUDs, infotainment systems have various functions, so physical control by task is required (Mathur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We then reviewed the full text of those 75 articles and excluded additional articles because they were either workshop papers (1), general conference proceedings descriptions (4), or not focused on VUIs (4; e.g., focused on gestures; Graichen et al, 2019). Furthermore, we eliminated 38 additional articles because they did not include older adult participants or focus on age or aging as a research consideration.…”
Section: Our Search Of Human Factors and Proceedings Of The Human Facmentioning
confidence: 99%
“…Compared to the touch screen system, the gestures resulted in fewer glances, as well as shorter glances when they did happen, towards the main control panel. As a result, participants reported the gesture-based system was better (Graichen, Graichen, & Krems, 2019). Similarly, Marz, Schwahlen, Geisler, & Kopinski (2016) concluded that gestures are easier to learn and use if they are similar to their touchscreen equivalent.…”
Section: Introductionmentioning
confidence: 98%
“…In situations where cognitive load or visual attention might be limited, gestures could be beneficial. Graichen, Graichen, & Krems (2019) conducted a study using a gesture-based interface in a car and compared it to a touchscreen system currently in vehicles. After completing a set of tasks varying in complexity while driving in a simulator, the participants rated the gestures as desired where the touch was neutral.…”
Section: Introductionmentioning
confidence: 99%